1993
DOI: 10.1038/hdy.1993.93
|View full text |Cite
|
Sign up to set email alerts
|

Mapping and characterization of quantitative trait loci affecting resistance against second-generation European corn borer in maize with the aid of RFLPs

Abstract: The European corn borer (Ostrinia nubilalis Hübner) is an important pest in the global production of maize (Zea mays L.). In this study, we mapped and characterized quantitative trait loci (QTLs) significantly affecting resistance against second-generation European corn borer (2ECB) and plant height with the aid of RFLP markers. A total of 300 F3 lines derived from cross B73 (susceptible) x B52 (resistant) were assayed for their parental F2 genotype at 87 RFLP loci. Field data on plant height and resistance ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
55
1
2

Year Published

1996
1996
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(68 citation statements)
references
References 32 publications
10
55
1
2
Order By: Relevance
“…Line CM625 was chosen as parent, because it had shown high susceptibility to S. sclerotiorum in artificial leaf infections (V. Hahn, unpublished data). However, as reported for other resistance traits (Scho¨n et al 1993;Bohn et al 2000), the susceptible parent P S also carried resistance alleles. For leaf lesion, significant transgression towards higher resistance of F 3 families was observed, suggesting that the susceptible parent CM625 contributed favorable alleles for resistance.…”
Section: Inheritance Of Resistance To Midstalk Rotmentioning
confidence: 91%
“…Line CM625 was chosen as parent, because it had shown high susceptibility to S. sclerotiorum in artificial leaf infections (V. Hahn, unpublished data). However, as reported for other resistance traits (Scho¨n et al 1993;Bohn et al 2000), the susceptible parent P S also carried resistance alleles. For leaf lesion, significant transgression towards higher resistance of F 3 families was observed, suggesting that the susceptible parent CM625 contributed favorable alleles for resistance.…”
Section: Inheritance Of Resistance To Midstalk Rotmentioning
confidence: 91%
“…During the past two decades, DNA molecular markers have been successfully used to map loci controlling quantitative trait variations. Depending on the hostparasite interaction considered, from two (Landry et al 1992) to seven (Schön et al 1993) QTL were identified, contributing to quantitative variations in disease resistance. Analyses of QTL associated with resistance to extension of the S. sclerotiorum mycelium on sunflower capitula and leaves, using molecular markers, have already been made by Mestries et al (1998).…”
Section: Introductionmentioning
confidence: 99%
“…This has been observed for morphological traits in tomato (Paterson et al, 1991) and for response to the disease gray leaf spot (caused by Cercospora zeaemaydis Tehon & Daniels) in maize . In contrast, maize studies have shown relatively consistent QTL detection across diverse environments for grain yield , morphological traits , and second generation European com borer resistance (Schon et al, 1993). These differences in consistency may be attributable to the biology of the traits, progeny and environment sampling variation, and QTL detection methods and threshold levels .…”
Section: Introductionmentioning
confidence: 77%
“…second generation European com borer resistance (Schon et al, 1993), and northern com leaf blight {Setosphaeria turcica) resistance (Freymark et al, 1993;Dingerdissen et al. 1996).…”
Section: Qtl Detection Across Environmentsmentioning
confidence: 99%
See 1 more Smart Citation